2015
DOI: 10.1038/srep14168
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of selection in tilapia revealed by whole genome resequencing

Abstract: Natural selection and selective breeding for genetic improvement have left detectable signatures within the genome of a species. Identification of selection signatures is important in evolutionary biology and for detecting genes that facilitate to accelerate genetic improvement. However, selection signatures, including artificial selection and natural selection, have only been identified at the whole genome level in several genetically improved fish species. Tilapia is one of the most important genetically imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 57 publications
(70 reference statements)
6
39
0
Order By: Relevance
“…Our study revealed that the LD level declined to 0.05 at 4000 Kb 294 inter-marker distance and that decay patterns were similar between populations ( Figure 295 4). A previous study conducted by Hong Xia et al, (2015) reported similar LD patterns 296 for GIFT tilapia stocks collected from South Africa, Singapore and China. Using 297 microsatellite loci Sukmanomon et al, (2012) estimated LD means in terms of 298 disequilibrium coefficient (D') of 0.05 for a GIFT population originally from the 299…”
Section: Linkage Disequilibrium and Effective Population Size 271supporting
confidence: 58%
“…Our study revealed that the LD level declined to 0.05 at 4000 Kb 294 inter-marker distance and that decay patterns were similar between populations ( Figure 295 4). A previous study conducted by Hong Xia et al, (2015) reported similar LD patterns 296 for GIFT tilapia stocks collected from South Africa, Singapore and China. Using 297 microsatellite loci Sukmanomon et al, (2012) estimated LD means in terms of 298 disequilibrium coefficient (D') of 0.05 for a GIFT population originally from the 299…”
Section: Linkage Disequilibrium and Effective Population Size 271supporting
confidence: 58%
“…The weight of tilapia fillet contributes heavily towards the yield per fish, which is an important parameter in the aquaculture industry1828. Here, we report the first methylome of skeletal muscle tissue, including sexually dimorphic DMRs, in hybrid tilapia, which is genetically close to Nile tilapia2122. We discovered that MAPK/ERK signaling pathway overexpression in male tilapia was associated with superior growth rate in male tilapia.…”
mentioning
confidence: 90%
“…The superior growth rate of male tilapias has driven large sectors of the tilapia aquaculture industry to develop all-male tilapia populations for production using sex-reversal techniques18. In addition, the genome sequence of a Nile tilapia has been sequenced19, and other genomic resources, including microsatellites20, genome-wide SNPs2122, linkage maps232425 and QTL for important traits2526, are available. Hence, tilapia is a good model for studying the molecular mechanisms underlying SD.…”
mentioning
confidence: 99%
“…Tilapia is an important commercial fish in China, which is euryhaline fish species and it is the second most important fish after carps in aquaculture [14]. Owing to ease of aquaculture, marketability and stable market prices, the production of tilapia has quadrupled over the past decade [15], and which is promoted and farmed in more than 100 countries and regions [16].…”
Section: Introductionmentioning
confidence: 99%